Letter to Mayor Lopez, Mayor Pro Tem Pinkard, Councilman Holden, Councilman Maulhardt, and Councilman Zaragosa - Jane Tolmach:::::: (1997)
A brief letter requesting that city council gets rid of the hearing officer and instead delegates his powers to a seven member planning commission.